Specific c-Jun target genes in malignant melanoma. Issue 5 (3rd May 2016) - Schummer, Patrick; Kuphal, Silke; Vardimon, Lily; Bosserhoff, Anja K.; Kappelmann, Melanie
ABSTRACT: A fundamental event in the development and progression of malignant melanoma is the de-regulation of cancer-relevant transcription factors. We recently showed that c-Jun is a main regulator of melanoma progression and, thus, is the most important member of the AP-1 transcription factor family in this disease. Surprisingly, no cancer-related specific c-Jun target genes in melanoma were described in the literature, so far. Therefore, we focused on pre-existing ChIP-Seq data (Encyclopedia of DNA Elements) of 3 different non-melanoma cell lines to screen direct c-Jun target genes. Here, a specific c-Jun antibody to immunoprecipitate the associated promoter DNA was used. Consequently, we identified 44 direct c-Jun targets and a detailed analysis of 6 selected genes confirmed their deregulation in malignant melanoma. The identified genes were differentially regulated comparing 4 melanoma cell lines and normal human melanocytes and we confirmed their c-Jun dependency. Direct interaction between c-Jun and the promoter/enhancer regions of the identified genes was confirmed by us via ChIP experiments. Interestingly, we revealed that the direct regulation of target gene expression via c-Jun can be independent of the existence of the classical AP-1 (5´-TGA(C/G)TCA-3´) consensus sequence allowing for the subsequent down- or up-regulation of the expression of these cancer-relevant genes. In summary, the results of this study indicate that c-Jun plays a crucial role in the development and progression of malignant melanoma via direct regulation of cancer-relevant target genes and that inhibition of direct c-Jun targets through inhibition of c-Jun is a potential novel therapeutic option for treatment of malignant melanoma.